Stavropol Television News as a Means of Modeling the Regional Media Agenda (Proceedings of Southern Federal University. Philology, 2018)
Elena N. Larionova (Stavropol, Russian Federation)In modern society, the reality shaped by TV, can be seen as one of the most effective tools of formation picture of the world as the individual and society as a whole. This article examines the phenomenon of information resources in regional aspect. The work is devoted to the analysis of news programmes of television channels Stavropol «ItsTV», «STRC «Stavropol»» and «26 region» and to identify the degree of their influence on the design of regional mediapoint. The news create a special TV reality, which, in its turn, has a significant influence on the formation of the world picture of the audience. For people receiving the main flow of information only from their everyday life and screen, it was TV events become structural in the formation of their own mediapoint. Because, in reality, the media cannot cover all events in the world, they are filtered in accordance with their own objectives and present. In this regard, the author believes it is important to have multiple television media in the same region, since this fact contributes to the fact that the air will be affected as many of the regional events and the viewer will form a more complete information picture. The article considers how different phenomena are devoted to the Stavropol news, or they offer the audience information about the same events.Key words: agenda, media agenda, information agenda, regional news, Stavropol television.DOI 10.23683/1995-0640-2018-3-184-194